2019
DOI: 10.1038/s41563-019-0536-8
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrophilic microporous membranes for selective ion separation and flow-battery energy storage

Abstract: Membranes with fast and selective ion transport are widely used for water purification and devices for energy conversion and storage including fuel cells, redox flow batteries, and electrochemical reactors.However, it remains challenging to design cost-effective, easily processed ion-conductive membranes with well-defined pore architectures. Here, we report a new approach to designing membranes with narrow molecular-sized channels and hydrophilic functionality that enable fast transport of salt ions and high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
232
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(236 citation statements)
references
References 58 publications
3
232
1
Order By: Relevance
“…The presence of this base then causes a lower degree of polymer protonation and 4− is immobilised. The absence of a voltammetric response when attempting immobilisation of Fe(CN) 6 4− without protons into PIM-EA-TB is consistent with the recently reported low permeation of Fe(CN) 6 4− under conditions of redox flow battery application [52].…”
Section: supporting
confidence: 89%
“…The presence of this base then causes a lower degree of polymer protonation and 4− is immobilised. The absence of a voltammetric response when attempting immobilisation of Fe(CN) 6 4− without protons into PIM-EA-TB is consistent with the recently reported low permeation of Fe(CN) 6 4− under conditions of redox flow battery application [52].…”
Section: supporting
confidence: 89%
“…Song et al used another amidoxime-containing PIM membrane (Figure 1b, AO-PIM-1 and AO-PIM-SBF) for K 4 [Fe(CN) 6 ]/DHAQ ARFB (Figure 7a-c). [25] They found that the microporosity of polymers and the content of amidoxime functionality show a strong correlation with battery performance (Figure 7c-f). The increase in BET surface area or AO functional group content could dramatically decrease the membrane resistance, thereby improving the energy efficiency and power density of the corresponding cells.…”
Section: Hpims For Aqueous Redox Flow Batteriesmentioning
confidence: 94%
“…[24] With the same method, Tan et al successfully modified the spirobifluorene-containing PIM (PIM-SBF) and obtained AO-PIM-SBF. [25] The hydrophilic amidoxime group can be either positively charged or negatively charged in aqueous solutions, depending on pH. It is positively charged at pH below 4 and becomes negatively charged when the pH is above 13.…”
Section: Post-synthetic Modification To Introduce Hydrophilic Moietiesmentioning
confidence: 99%
“…[53] Even hydrophobic regular structurem aterials, such as PIMs, have been modified utilizing their distinct pore sized to endow hydrophilicity.H ydrophilic ordered channels and well-controlled thickness of the selective layer all can induce ah ighi onic conductivity. [86] Due to the above virtues, composite membranes with ordereds elective layersh old great potentiala sm embranes in FBs with high efficiencies (Coulombic efficiency,v oltage efficiency,a nd energy efficiency were all included) and low capacity decay. [86] Kim et al [20] designed aP TFE composite membranew ith a graphene oxide framework (GOF) selectivel ayer.Across-linked GOF with around0 .4 mmt hickness was formed owing to the reaction between GO nanosheets and ethylenediamine (EDA).…”
Section: Composite Membranes In Fb Applicationmentioning
confidence: 99%